Quantifying Brexit: from ex post to ex ante using structural gravity - Gabriel Felbermayr; Jasmin Gröschl; Marina Steininger (Review of World Economics, 2021)
Exploiting changes in the geography of economic integration in Europe, this paper quantifies the effects of Brexit from ex post to ex ante using structural gravity. By isolating the directional treatment effects of EU agreements for the UK, the analysis reveals important heterogeneity across agreements, sectors, and within pairs. We find that these directional effects matter for the size and distribution of the welfare effects of Brexit—the withdrawal of the UK from EU agreements resulting into a return of trade costs to the situation quo ante. We make this point with the help of a modern multi-sector trade model that is able to capture inter- and intranational production networks. In line with other papers, the welfare costs of Brexit are higher in the UK than in most other EU countries. However, heterogeneity tends to attenuate overall costs while giving rise to substantial heterogeneity between EU27 members and sectors. A scenario that could shift bargaining power eliminates asymmetries in the costs of Brexit as soon as the UK fully liberalizes its market.
Keywords: F15; F17; N74; 330; Structural gravity; General equilibrium; Treatment heterogeneity; Brexit